Changes in orexinergic immunoreactivity of the piglet hypothalamus and pons after exposure to chronic postnatal nicotine and intermittent hypercapnic hypoxia. (5th May 2016) - Hunt, Nicholas J.; Russell, Benjamin; Du, Man K.; Waters, Karen A.; Machaalani, Rita
Abstract: We recently showed that orexin expression in sudden infant death syndrome (SIDS) infants was reduced by 21% in the hypothalamus and by 40–50% in the pons as compared with controls. Orexin maintains wakefulness/sleeping states, arousal, and rapid eye movement sleep, abnormalities of which have been reported in SIDS. This study examined the effects of two prominent risk factors for SIDS, intermittent hypercapnic hypoxia (IHH) (prone‐sleeping) and chronic nicotine exposure (cigarette‐smoking), on orexin A (OxA) and orexin B (OxB) expression in piglets. Piglets were randomly assigned to five groups: saline control ( n = 7), air control ( n = 7), nicotine [2 mg/kg per day (14 days)] ( n = 7), IHH (6 min of 7% O2 /8% CO2 alternating with 6‐min periods of breathing air, for four cycles) ( n = 7), and the combination of nicotine and IHH (N + IHH) ( n = 7). OxA/OxB expression was quantified in the central tuberal hypothalamus [dorsal medial hypothalamus (DMH), perifornical area (PeF), and lateral hypothalamus], and the dorsal raphe, locus coeruleus of the pons. Nicotine and N + IHH exposures significantly increased: (i) orexin expression in the hypothalamus and pons; and (ii) the total number of neurons in the DMH and PeF. IHH decreased orexin expression in the hypothalamus and pons without changing neuronal numbers. Linear relationships existed between the percentage of orexin‐positive neurons and the area of pontine orexin immunoreactivity of control and exposure piglets. These results demonstrate that postnatal nicotine exposure increases the proportion of orexin‐positive neurons in the hypothalamus and fibre expression in the pons, and that IHH exposure does not prevent the nicotine‐induced increase. Thus, although both nicotine and IHH are risk factors for SIDS, it appears they have opposing effects on OxA and OxB expression, with the IHH exposure closely mimicking what we recently found in SIDS. Abstract : Percentage change of orexin immunoreactivity in air control (AC), nicotine (Nic), intermittent hypercapnic hypoxia (IHH) and combined treatment (N + IHH) groups as compared with the saline control group in the in the central tubular hypothalamus of piglets; the decreased orexin immunoreactivity in SIDS was observed by Hunt et al . (2015b). Data represent the mean percentage change.